Pengembangan Potensi Kawasan Hutan dengan Tujuan Khusus (KHDTK) Gunung Bromo UNS Menjadi Destinasi Wisata Edukasi di Kabupaten Karanganyar - Fitri Lutfi’ah, Amila; Tias, Fera Cahyaning; Nasta Kinarya, Caroline Gema; Inaiya, Agstalia Reska; Dheananda, Azahra Aulia; Nugraheni, Nadiya Kusuma; Askuri, Rida Fatwa; Mevita, Dunya Fara; Marimin, Marimin; Wijaya, Deria Adi (Tourism Scientific Journal, 2023)
KHDTK Mount Bromo is a forest area that has a variety of rare trees and some kinds of animals, so it is often visited by tourists.The condition exists as an area of education, research and dedication to society manifestations of the development of science and technology, as well as providing well-being and income to the surrounding communities. Several activities are being carried out, including conservation efforts through reforestation and organizations: Kelompok Tani Hutan (KTH), Masayarakat Peduli Api (MPA) as well as cooperation with other units and agencies. The educational tourism education policy implementation programme has been developed effectively in increasing the number of visitors. The research method used is qualitative descriptive. Tourism activities are carried out through the development strategy of nature tourism for educational tourism. Educational tourism activities through outbond that have an impact such as introduction of flora and fauna, honey harvesting for SD and SMP children. The highrope available is one of the promoters of educational tourism that aims to train balance, concentration, and strength. The area also provides MICE facilities for cultural tourism performances and also special interests such as special offroad trails. The strategic area is close to the city and its easy accessibility can be developed integrated educational tourism.